Peran Penyuluh Pertanian Lapangan Pada Kelompok Tani Padi Sawah Teguh Bersinar Di Desa Kaneyan Kecamatan Tareran Kabupaten Minahasa Selatan - Pratasis, Sutrika Marlina; Tambas, Jane Sulinda; Sondakh, Mex Frans Lodwyk (AGRI-SOSIOEKONOMI, 2023)
This study aims to find out and see how the role of field agricultural extension workers, especially in the lowland rice farmer groups in Kaneyan Village, Tareran District, South Minahasa Regency. The research was conducted in Kaneyan Village, Tareran District, South Minahasa Regency in July 2022. The data collection method was obtained from primary data through direct interviews using a questionnaire, and secondary data was obtained from agencies related to research and various literature that was in accordance with the research objectives. The sampling method in this research is purposive sampling (intentionally). Determination of the sample of 10 respondents who are the head of agricultural extension workers and the Teguh Bersinar rice field farmer group. The results of the study showed that the extension workers had carried out their duties properly. This can be seen from the majority of respondents who stated that extension agents had guided and facilitated farmers to be better.